Resource Allocation for Full-Duplex Relay-Assisted Device-to-Device Multicarrier Systems - Shuping Dang; Coon, Justin P.; Gaojie Chen (IEEE wireless communications letters, 2017)
This letter analyzes the resource allocation problem for full-duplex relay-assisted device-to-device (D2D) multicarrier systems, where multiple D2D user groups (UGs) coexist in an underlaying manner. We formulate the optimization problem, which takes the maximization of the system throughput as an objective. Two resources, i.e., subcarrier and transmit power are considered to be appropriately allocated to UGs in order to meet the objective. The formulated problem can be independently divided into a quasi-concave problem and a mixed binary integer programming (MBIP) problem. The MBIP problem is NP-hard. Therefore, to solve this problem efficiently by standard optimization techniques, we propose an alternative algorithm, which is the linear relaxation of the MBIP problem. Then, we mathematically prove and numerically verify the equivalence of the MBIP problem and its linear relaxation. By this way, the resource allocation for UGs can be carried out by a small amount of computational overhead.